Topical issues regarding the causality of construction incidents. Issue 4 (5th June 2019) - Butyrin, Andrey Yurievich; Stativa, Ekaterina Borisovna; Lyubimenko, Dmitrii Petrovich; Fomenko, Aleksandr Evgenevich; Krylova, Mariya Igorevna
Abstract : This paper considers issues related to the establishment of the presence and types of causal connections among events, actions, phenomena and processes investigated based on technical forensic construction expertise during the building of judicial cases. The authors, practising forensic experts, disclose the common principles that allow for the development of universal approaches to establishing the causes of accidents in construction; determining the causes of the initiation and progression of destructive processes in the bearing and enclosing structures of raised and operated buildings, structures and constructions; and establishing conditions and circumstances for the given mode of operation failure of engineering maintenance systems of apartment houses, offices and industrial premises. Consistently, the paper presents and gives examples from practice of such causal relationships as 'immediate' and 'direct'; the concept of 'sufficiency of conditions' is revealed with respect to the negative consequences that have occurred with the alternative possibility of their occurrence due to the influence of other factors; and the value of the relationship in time of certain actions and a specific event is determined.